Catalytic transfer hydrogenation of furfural to furfuryl alcohol using easy-to-separate core–shell magnetic zirconium hydroxide. (26th January 2021) - Hou, Pan; Ma, Mingwei; Zhang, Peng; Cao, Jingjie; Liu, Hui; Xu, Xingliang; Yue, Huijuan; Tian, Ge; Feng, Shouhua
Abstract : A core–shell magnetic catalyst is applied for the hydrogenation of furfural and other carbonyl compounds using isopropanol as H-donor. Abstract : A hollow core–shell magnetic zirconium hydroxide catalyst was synthesized and employed for the catalytic transfer hydrogenation (CTH) ofnumerous biomass-derived platform molecules (furfural and other carbonyl compounds). 93.9% conversion of furfural and 97.3% selectivity of furfuryl alcohol was achieved under mild reaction conditions (160 °C, 4 h, 0.1 g catalyst) with 2-propanol as the H-donor. After 7 times of reaction cycles, the catalyst retained excellent conversion (91.1%) and selectivity (97.8%) and no structural damage was found. Furthermore, a scale-up experiment was carried out, and the results proved that the catalyst has a prospect for industrial applications in the CTH reaction.